2020
DOI: 10.3390/catal10111338
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Anodic Copper Oxides as Catalysts in Electrochemical and Photoelectrochemical Reactions

Abstract: Recently, nanostructured copper oxides formed via anodizing have been intensively researched due to their potential catalytic applications in emerging issues. The anodic Cu2O and CuO nanowires or nanoneedles are attractive photo- and electrocatalysts since they show wide array of desired electronic and morphological features, such as highly-developed surface area. In CO2 electrochemical reduction reaction (CO2RR) copper and copper-based nanostructures indicate unique adsorption properties to crucial reaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 183 publications
(234 reference statements)
0
21
0
Order By: Relevance
“…[46,47] C 2 formation on OCÀ Cu and FAÀ Cu can be ascribed to the high surface roughness of the annealed Cu (as seen in Table 3) and higher electrochemically active surface area. [41] Stability measurements performed for 3 h showed an initial reduction of Cu oxides followed by constant current density, as illustrated in Figure S7. The characterisation by XRD ( Figure S8) and SEM ( Figure S9) of the oxidised Cu samples before and after CO 2 reduction depicts the reduction of oxides to the metal in par with the literature results, [3] and a newly formed Cu surface helps in C 2 formation.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…[46,47] C 2 formation on OCÀ Cu and FAÀ Cu can be ascribed to the high surface roughness of the annealed Cu (as seen in Table 3) and higher electrochemically active surface area. [41] Stability measurements performed for 3 h showed an initial reduction of Cu oxides followed by constant current density, as illustrated in Figure S7. The characterisation by XRD ( Figure S8) and SEM ( Figure S9) of the oxidised Cu samples before and after CO 2 reduction depicts the reduction of oxides to the metal in par with the literature results, [3] and a newly formed Cu surface helps in C 2 formation.…”
Section: Resultsmentioning
confidence: 94%
“…[40] However, with the increase in oxidation temperature, C 2 (ethane and ethylene) formation reached a plateau with the increase in the thickness of the electrode ( Figure S6), emphasising that the thickness of the oxide layer governs the product formation rate. [3] In the literature, the selectivity of oxide-derived copper towards C 2 products has been attributed to several factors, such as (i) a higher local pH at the catalyst surface, favouring the CÀ C coupling pathway over the formation of C 1 product; [41] (ii) more grain boundaries, defect sites and crystal planes; and (iii) the presence of oxides, which provide Cu sites with multiple valences to increase the catalytic activity. [37,42,43,44] Eilert et al reported the existence of subsurface oxygen during CO 2 reduction-enhanced C 2 selectivity because of changes in the electronic structure of the Cu, improving the binding of CO. [45] Furthermore, the selectivity for C 2 products depends on the higher surface roughness, leading to increased local current density and the mode of CO 2 adsorption during the reduction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Papers essentially describing synthetic routes, a material's characterization, or the investigation of a material's properties are not addressed in this review. For such topics, we recommended the excellent review papers in the anodic oxide field [2,8,[34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%